Re-evaluation of the hCMEC/D3 based in vitro BBB model for ABC transporter studies - Balzer, Viktor; Poc, Pascal; Puris, Elena; Martin, Stefan; Aliasgari, Maryam; Auriola, Seppo; Fricker, Gert (European journal of pharmaceutics and biopharmaceutics, 2022)
The blood-brain barrier (BBB) represents one of the biggest hurdles for CNS related drug delivery, preventing permeation of most molecules, and therefore poses a major challenge for researchers in finding effective treatments for CNS diseases. The low permeability of molecules through the BBB is linked on one hand to the extreme tightness by tight junction (TJ) formation limiting the paracellular transport, and on the other hand to the presence of ATP-driven efflux pumps which actively transport unwanted compounds out of the brain. In this study we evaluated the applicability of the immortalized human cell line hCMEC/D3 for ABC transporter studies, focusing on the most expressed ABC transporters at the human BBB: P-glycoprotein (PGP, ABCB1), multidrug resistance protein 4 (MRP4, ABCC4) and breast cancer resistance protein (BCRP, ABCG2). Therefore, a two-step screening method was applied, consisting of a regular uptake assay (96-well format) and bidirectional transport studies, using a transwell system as in vitro simulation of the human BBB. In conclusion, the hCMEC/D3 based in vitro BBB model is well suited to screen drug candidates for ABC transporter interactions on the basis of a regular uptake assay, but in terms of transcellular permeability studies the cell line is limited by a lack of sufficient junctional tightness.
Gesehen am 26.07.2022